2011
DOI: 10.1258/ebm.2010.010140
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of histone variant H2A.1 and cellular transformation are related in N-nitrosodiethylamine-induced sequential hepatocarcinogenesis

Abstract: Histones through a complex repertoire of non-allelic variants and their post-translational modifications regulate gene expression. Though alterations in histone-modifying enzymes and post-translational modifications of histones have been studied in cancer, expression of histone variants has not been clearly associated with dedifferentiation and malignant transformation of hepatocyte in vivo. In the present work, the pattern of variants of histones was investigated during N-nitrosodiethylamine (NDEA)-induced he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 24 publications
1
32
0
1
Order By: Relevance
“…On HIRA depletion, the induction of VEGFR1 and other angiogenic genes is impaired. A direct link between histone variant expression and cancer development has recently been drawn by Khare et al (2011). They showed that during sequential development of hepatocellular carcinoma, H2A and H2A.1 are overexpressed, whereas H2A.2 is decreased.…”
Section: Histone Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…On HIRA depletion, the induction of VEGFR1 and other angiogenic genes is impaired. A direct link between histone variant expression and cancer development has recently been drawn by Khare et al (2011). They showed that during sequential development of hepatocellular carcinoma, H2A and H2A.1 are overexpressed, whereas H2A.2 is decreased.…”
Section: Histone Variantsmentioning
confidence: 99%
“…They showed that during sequential development of hepatocellular carcinoma, H2A and H2A.1 are overexpressed, whereas H2A.2 is decreased. The increased expression of H2A.1 has been linked to hyperproliferation (Khare et al, 2011). In addition, the histone variant macroH2A appears to suppress tumor progression of malignant melanoma through regulation of CDK8 (Kapoor et al, 2010).…”
Section: Histone Variantsmentioning
confidence: 99%
“…11,13 The animals (22-24 weeks) for liver regeneration studies were subjected to two-third PH. The surgeries were performed under sterile conditions as per protocol.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…10 Previous report from laboratory has also shown over-expression of H2A.1 with decrease in expression of H2A.2 during de-differentiation of mature hepatocytes to HCC. 11 Recently, replication-dependent histone coded by human HIST1H2AC gene locus, sequence similar to rat H2A.1, has been associated with cell proliferation and tumorigenicty of bladder cancer cells. 12 In order to define alteration in H2A.1 and H2A.2 variants in the same organ system during development, de-differentiation, and normal cellular proliferation, their comparative profiling at RNA and protein level was studied during liver regeneration post PH and differentiating embryonic liver.…”
Section: Introductionmentioning
confidence: 99%
“…Z and macroH2A have also been reported to express aberrantly [18][19][20] . Also, histones proteins can undergo a variety of PTMs some of which are methylation (me), acetylation (ac), ubiquitylation (ub), sumoylation (su) and phosphorylation (ph) on specific amino acid ( Figure 1) [10] .…”
Section: Histone Ptms: a Dynamic Processmentioning
confidence: 99%